Pengaruh Suhu Pemanasan Terhadap Karakteristik Bioplastik Dari Pati Biji Durian - Dodit Ardiatma; Hana Marisa Kurniareja (DPPM Universitas Pelita Bangsa, 2022)
Plastic litter is an environmental problem at the moment. Today's widely used plastic is a synthetic polymer plastic made from petroleum that is difficult to dissolve in nature. The concrete step needed to address the environmental problem is to use and develop rapidly bioplastik plastic. Bioplastik plastic (bioplastic) is a bioplastik plastic that is bioplastik by microorganisms that break down. In this study the production of a bioplastic is made from durian seed starch. Selection of materials is based on biodegradability in the environment more easily and abundant raw materials available, and lack of innovation in the use of durian waste. Bioplastic production begins with an 2.5 ounce [2.5 g] of durian seed being diluted by 50 ml [50 ml] aqudest, then stirred and heated with 50oC, 60oC, 70oC, 80oCand 90oC, mix kitchambers 1ml and 0.2 - ml glycerol and mix them back for 10 minutes, then pour a bioplastic solution into print, Removing the plastic from the glass plate for characteristic testing. The results of the analysis show that warming temperatures in the gelatinization process affect strong value drag, elongation value and water-resistant value, which, as rising temperature of warming, increases the strong value of drag, elongation value and water resistance. The highest attractive value is found in the 90oCtemperature variation of 54.27 mpa. The highest concentration of elation is 16.4, 10 percent. The best water resistance lies in a 90oCwarming variation of 21.21 % and the fastest minus time of degradation found in a 50oCtemperature variation of 8 days. Keywords: Durian Seeds, Gelatinization, Starch, Biodegradable Plastic